Is it the Taking Part that Counts? Access to Lifelong Learning Opportunities in Germany's Regime of Dis/Ability - Silke Schreiber-Barsch (University of Bologna, 2019)
This paper reveals why the issue of transforming the system of lifelong learning towards an 'inclusive education system at all levels and lifelong learning' (United Nations, 2006, p. 16), due to national ratifications of the UN Convention on the Rights of Persons with Disabilities (2006), cuts right to the core of democratic societies and national policy agendas. Following the socio-spatial works by Löw (2001; 2008), the example of the German lifelong learning arena serves to illustrate the benefit of spatial theory in the adult education discourse. Empirical findings of a qualitative research design allow insights into how access to a place of learning is interpreted and organised by adult education professionals. It opens up an understanding of who gains access to public adult education institutions and, imperatively, why access is not merely a pedagogical issue, but a negotiation of citizenship and politics and is, thus, of a genuine political nature.